T-SHIRT INDIEGUERILLAS SEBAGAI MEDIA KOMUNIKASI VISUAL - Aji Windu Viatra (UNIVERSITAS INDO GLOBAL MANDIRI, 2017)
Clothing style is often associated with the perception of the identity of the person who describes the class, profession, origin, gender and social. Appearance in the way we dress is interpreted to make a mark against the communicant interaction act indirectly and what should make us behave toward others. Apparel is seen to have a communicative function, in the Science Communication process can communicate through visual and verbal media such material in this study that T-shirts or T-shirts. This study will analyze the T-shirts (T-shirt) Indieguerillas as a medium of visual communication can be a major influence and interpret a t-shirt design that can speak, act and understand the meaning of a sign as desired by the manufacturer of the shirt. Research